"Keep It to Yourself": A Qualitative Study of HIV Disclosure Perspectives Among Older Adults Living With HIV in South Carolina Who Are Childhood Sexual Abuse Survivors. (17th September 2022) - Brown, Monique J.; Nkwonta, Chigozie A.; James, Titilayo; Kaur, Amandeep; Hart, Mackenzie J.; Addo, Prince Nii Ossah; Adeagbo, Oluwafemi A.
Abstract: HIV disclosure is an important consideration for people living with HIV. The prevalence of childhood sexual abuse (CSA) may range from 16% to 22% among older adults living with HIV. There is a dearth of research on HIV disclosure among older CSA survivors. Therefore, the aim of this study was to qualitatively examine HIV disclosure among older CSA survivors living with HIV. Twenty-four CSA survivors living with HIV (aged 50–67 years) participated in in-depth, semistructured interviews. Data were analyzed thematically, and the iterative coding and analytic process included discussion of initial thoughts and key concepts, identification and reconciliation of codes, and naming of emergent themes. Four themes emerged: (a) secrecy/not planning to disclose HIV; (b) disclose HIV regardless; (c) disclose HIV depending on the person; and (d) disclose HIV depending on the circumstance. Lack of disclosure may be due to HIV-related stigma. HIV disclosure intervention programs may be beneficial for this population